2004
DOI: 10.1093/aob/mci034
|View full text |Cite
|
Sign up to set email alerts
|

Young Daughter Cladodes Affect CO2 Uptake by Mother Cladodes of Opuntia ficus-indica

Abstract: Daughter cladodes significantly hasten the effects of drought on mother cladodes by competition for the water supply and thus decrease daily carbon gain by mother cladodes, mainly by inhibiting phase IV of CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
2
25
0
1
Order By: Relevance
“…In addition, under conditions of drought, heat stress and radiation, the chlorenchyma loses significant amount of water and the cladode begins to exhibit rough aspect and loss of its characteristic green color (Becerril & Valdivia, 2006), indicating loss of chlorophyll (Pimienta-Barrios et al, 2005). These descriptions corroborate with the results of fluorescence found in the present study for the dry season.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, under conditions of drought, heat stress and radiation, the chlorenchyma loses significant amount of water and the cladode begins to exhibit rough aspect and loss of its characteristic green color (Becerril & Valdivia, 2006), indicating loss of chlorophyll (Pimienta-Barrios et al, 2005). These descriptions corroborate with the results of fluorescence found in the present study for the dry season.…”
Section: Resultssupporting
confidence: 90%
“…Nonetheless, due to the effect of organic fertilization, new cladodes grew, which undergo more damage to the photosynthetic apparatus under drought conditions, resulting in reduction of efficiency and quantum yield. Daughter cladodes represent strong sink organs and cause physiological stress on mother cladodes during the dry season (Zañudo-Hernández et al, 2010), with reduction in the daily C gain and relative water content in mother cladodes, suggesting water movement from mother to daughter (Pimienta-Barrios et al, 2005). In addition, CO 2 assimilation is more affected in the phase IV of CAM (Nobel, 2001) (net CO 2 absorption in late afternoon) by the combined effects of daughter cladodes and drought.…”
Section: Resultsmentioning
confidence: 99%
“…Pimienta-Barrios et al [32] found in O. ficus-indica a lower concentration of TPCs in cladodes bearing either eight or more daughter cladodes and explained it as a result of competition for resources between parent and daughter cladodes [33]. We obtained a similar result in that almost all of the parental first-level cladodes produced only one daughter.…”
Section: Discussionsupporting
confidence: 80%
“…This is dominated by nocturnal changes in chlorenchyma osmotic pressure and not by transpiration (Schulte et al 1989). Younger developing cladodes of O. ficus-indica, which initially may be C 3 -like performers, can be provided with water from the underlying mother cladodes (Pimienta- Barrios et al 2005). They have lower water potentials than the mature underlying cladodes maintaining a water potential gradient for supply of water to the young cladodes via the xylem.…”
Section: Global Distributionmentioning
confidence: 99%